A new species of Salvia (Lamiaceae) from Northern Peru - Sagástegui Alva, Abundio (2012)
Salvia vargas-llosae Sagást. & E. Rodr. sp. nov. is described and illustrated as a new species of Salvia L. (Lamiaceae) from the Andes of Northern Peru (province of Celendin, department of Cajamarca). This new species belongs to the section Cylindriflorae (Epling) Epling and typically restricted to the region jalca (Sendamal- Kumulca-Challuayaco) above the 3000 m of altitude and apparently endemic to this part of the country. It is discussed with its closest relatives and additionally data on its geographical distribution, ecology and state of conservation are provided.